PERAN KELUARGA DALAM ASUPAN NUTRISI LANSIA DI DESA KEBONAGUNG KECAMATAN PURI KABUPATEN MOJOKERTO - Istianto, Anjar; Kartiningrum, Eka Diah (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2012)
Family plays an important role in planning and presenting a balanced diet for the elderly to fulfillment the nutritional. The purpose of this study was to identify family role of nutrition in elderly. This research used household suvey. The family role of nutrition all needs in elderly as variable in this research. Families with elderly amounted to 37 respondents as samples which is selected by consecutive sampling. Collecting data using questionnaires, the data obtained and analyzed using T score. The results showed that most respondents have a positive role to fulfill the nutritional needs of elderly people was about 19 respondents (51.4%). Families indicated a positive role by planning meals and preparing a balanced diet for the elderly in everyday life. Planning involved setting eating meals and beverages, food ingredients and size selection of food consumption, while the preparation of a balanced diet for the elderly include, restriction of certain food ingredients for the health of the elderly, limiting the size of the consumption of carbohydrates, proteins, and other food. The role of the family was very important for the health of the elderly, families that play a positive role in fulfilling the nutritional needs of older adults, the elderly will be spared from a variety of degenerative diseases and less susceptible to infectious diseases. The conclusion of this study was the validity of nutrient intake will influence the nutritional status of elderly which is depends on the role of nutrition to elderly families.Keyword: Roles, Nutrition, Elderly